REFORMULASI PEMBUKTIAN KEKERASAN SEKSUAL: Perbandingan Hukum Nasional dan Hukum Islam - Haniyah, Haniyah; Atmari, Atmari (MAQASHID, 2025)
In the midst of increasing public awareness of sexual violence, Indonesia is still faced with serious problems in proving it in the legal realm. Many cases stop halfway or end without justice because of the difficulty of meeting formal evidence such as visum or eyewitnesses which, in practice, are nearly impossible to find in sexual violence that occurs in covert, under pressure, or power relations. This study explores how the system of proof of sexual violence can be built to be more in favor of the victim, and the extent to which Islamic legal values, especially maqāṣid al-sharī'ah, can provide relevant and contextual solutions.  In answering this study, a normative-comparative approach is used with a literature study method on laws and regulations, the doctrine of fiqh jināyah, and the principles of maqāṣid. The results show that the Islamic legal system, especially in the context of ta'zīr, opens up a wider and more flexible space for proof through the use of qarā'in (strong indications) as well as considerations of the benefit and protection of victims in obtaining justice. By combining the substantive justice values of maqāṣid al-sharī'ah and the progressive spirit of the violent crime law (TPKS Law), this study offers an alternative model of proof that is more responsive, humane, and inclusive. These findings are expected to be important inputs in formulating an Indonesian criminal law system that is more adaptive to the vulnerability of victims and able to respond to the challenges of justice in today's world.